Acute low and moderate doses of caffeine improve aerobic endurance but not throwing velocity in trained female handball players - Yildirim, U. C. (International Journal of Disabilities Sports and Health Sciences, 2023)
Handball is a high-intensity team sport requiring muscle power and high aerobic capacity. Caffeine is a commonly used ergogenic aid known to enhance sports performance. However, its effects on female handball players remain unclear. This study aims to investigate the effects of acute low (LCAF) and moderate (MCAF) doses of caffeine intake on aerobic endurance and throwing velocity in trained female handball players. Fifteen trained female handball players participated in this randomized, double-blind, crossover study. Participants completed four sessions, including a familiarization session and three test sessions. The test sessions involved ingesting either 3 mg/kg (LCAF) or 6 mg/kg (MCAF) of caffeine or a placebo (PLA). Throwing velocity and aerobic endurance were measured using a hand radar gun and the Yo-Yo Intermittent Recovery Test Level 1, respectively. The results showed a significant improvement in aerobic endurance with both LCAF and MCAF doses of caffeine compared to the PLA condition (f= 5,993; p= ,014; n2= ,480). However, there was no significant difference in throwing velocity between the caffeine and placebo conditions (f= ,040; p= ,961; n2= ,006). Acute LCAF and MCAF doses of caffeine supplementation can enhance aerobic endurance but do not affect throwing velocity in trained female handball players. These findings contribute to the limited literature on the effects of caffeine in trained female handball players and suggest that caffeine may be a useful nutritional strategy for improving performance in this sport.